Platelet function and blood coagulation system status in childhood essential thrombocythemia - Dmitrii M. Polokhov; Nikolay M. Ershov; Anastasia A. Ignatova; Evgeniya A. Ponomarenko; Marina V. Gaskova; Pavel A. Zharkov; Daria V. Fedorova; Alexandr V. Poletaev; Elena A. Seregina; Galina A. Novichkova; Nataliya S. Smetanina; Mikhail A. Panteleev (Platelets, 2020)
Childhood essential thrombocythemia (ET) is a rare chronic myeloproliferative disorder. The quality of life of ET patients may decrease as a result of ischemic and hemorrhagic complications of unclear origin. Our goal was to characterize the hemostatic system in children with ET. We genotyped and investigated blood samples from 20 children with ET in a prospective case series study using platelet aggregation, functional flow cytometry (FC) assay and standard clotting assays. Three children had a JAK2V617F mutation, 4 had mutations in CALR and 13 were triple-negative. Myelofibrosis in stage 1-2 was detected in 3 children. Three patients had bleeding episodes and seven had ischemic events. Aggregation in response to collagen, adenosine diphosphate, and ristomycin was decreased in all patients. In FC, significant changes in the whole patient group compared to the healthy children control group were decrease in the resting forward scatter and PAC1 binding (activated GPIIb/IIIa) level. For the activated platelets, dense granules release (by mepacrine), PAC1, and GPIIb/IIIa levels were significantly decreased. GPIb/V/IX, P-selectin, and phosphatidylserine levels manifested only moderate differences. Forward and side scatter changes in response to stimulation (representing shape change) and dense granules release were significantly lower in the 3 patients with bleeding than in the 17 patients without hemorrhage. Activated partial thromboplastin time was slightly prolonged, prothrombin index was slightly shortened and thrombin time was normal, while fibrinogen was mildly decreased in the ET patients. It could be concluded that the observed platelet function defects could be related to bleeding in ET, and be potentially used as a marker.